Schisandra henryi a species with high medicinal potential and pharmacological activities of dibenzocyclooctadiene lignans - Karolina Jafernik; Adam Kokotkiewicz; Halina Ekiert; Maria Łuczkiewicz; Agnieszka Szopa (Polish Pharmaceutical Society, 2023)
Schisandra henryi C.B. Clarke (family Schisandraceae), is a species endemic to China Yunnan Province. S. henryi is a little known plant in Europe and the United States. Few studies on the chemical composition of S. henryi, mainly by scientists from Chinese institutions, showed the presence of compounds belonging to lignans, triterpenoids and nortriprenoids. Recently, research by the team of the Department of Pharmaceutical Botany of the Jagiellonian University Medical College has highlighted the great potential of this species. Phytochemical, biological and biotechnological researches are conducted. The analysis of the chemical composition showed the presence of compounds from the group of dibenzylcyclooctadiene, aryltetraline and dibenzylbutane lignans as well as polyphenols - phenolic acids and flavonoids. An innovative aspect of the scientific work is in particular biotechnological research focusing on proposing biomass from in vitro cultures of S. henryi as a source for obtaining extracts and biologically active compounds, alternative to the hard-to-reach material collected from natural sites. The aim of the study was to review the scientific literature on research on S. henryi, with particular emphasis on its botanical, ecological and chemical characteristics, and biological properties of extracts and isolated compounds. In addition, the potential of biotechnological research conducted on in vitro cultures of S. henryi focusing on understanding their metabolic profile was signaled. The paper also presents a detailed characterization of dibenzocyclotadiene lignans specific for the Schisandraceae family. They are the subject of numerous scientific studies that confirm their valuable pharmacological properties. Particularly noteworthy are their hepatoprotective and hepatoregenerating properties, as well as: anti-inflammatory, neuroprotective, anticancer, antiviral, antioxidant, cardioprotective, antiosteoporotic and supporting the treatment of intestinal dysfunction.